Depending On The Dependency Claim - Balan, P (Journal of Malaysian and Comparative Law, 2019)
In 1846, the English Parliament enacted the first Fatal Accidents Act (Lord Campbell's Act) to create a major exception to the common law rule which was described in Baker v Bolton as, "In a civil court the death of a human being cannot be complained of as an injury". The Act, prompted by the increasing number of railway accidents, created a new cause of action which allowed specified dependants of a deceased person to sue the person who caused the deceased's death and claim damages for the pecuniary support that they had lost.